Alkaloid and Steroid from the Stem Bark of Jatropha curcas (Euphorbiaceae) - Gupta, Dipankar Das; Haque, Md Enamul; Islam, Md Nahidul; Rahman, Shafiqur; Hasan, AKM Mahbub; Shibib, Baigid Alam (Dhaka University Journal of Pharmaceutical Sciences, 2012)
The plant Jatropha curcas grows well in different parts of Bangladesh and used in many medicinal purposes locally. The alkaloid atherospermidine and a steroid stigmasterol were isolated from the ethyl acetate extract of the stem bark of J. curcas by a combination of column and preparative thin-layer chromatography over silica gel. The structures of these compounds were determined by spectroscopic analysis (UV, IR, 1H NMR and 13C NMR) and by comparison with published data. This is the first report of isolation of the alkaloid atherospermidine from this plant. DOI: http://dx.doi.org/10.3329/dujps.v10i1.10009 DUJPS 2011; 10(1): 9-11